A survey of global biosimilar implementation practice conducted by the International Society of Oncology Pharmacy Practitioners. (April 2020) - Foreman, Emma; Patel, Himanshu; Siderov, Jim; Harchowal, Jatinder; Bubalo, Joseph; Chan, Alexandre
Background: The International Society of Oncology Pharmacy Practitioners (ISOPP) Biosimilars Task Force was charged to develop educational activities and resources to assist members when implementing biosimilar medicines into their local practice. To facilitate the process, the task force conducted a survey in order to understand biosimilar implementation practice by ISOPP members across the world and the challenges that oncology pharmacists face when adopting biosimilars into their clinical practice. Methods: A cross-sectional survey was conducted between 20 April 2019 and 27 May 2019. Members of ISOPP and a number of national oncology pharmacy groups were invited to complete the survey. The survey contained 29 items and consisted of three sections: respondents' demographics, respondents' institutional practice relating to biosimilar implementation and post implementation practice at the respondents' institutions. Descriptive statistics were utilized to analyze the survey results. Results: A total of 265 ISOPP members were surveyed, with 50 members providing a response (response rate = 19%). In addition, 40 nonmembers participated in the survey, bringing the total to 90 respondents. The most common factors that influence the decision to implement use of a biosimilar as reported by respondents are medication costs/pricing (92%), available clinical data (73%), and product availability (63%). Respondents also commented on the barriers to biosimilar implementation at their institutions, which included a reluctance of prescribers to use biosimilars (due to the lack of familiarity or perceived inferiority), a reluctance to switch established patients from an originator to a biosimilar and the preferences of insurance companies or funding bodies. Conclusion: The results of this survey reinforce the need for greater education and training for health care professionals in the use of biosimilars, the importance of sharing good practice, and a need for standardization.